Current Status of Research on Mobile Banking: An Analysis of Literature - Ashique Ali K. A; Rameshkumar Subramanian
The banking industry across the globe has been undergoing severe transformation due to the development in the field of information and communication technology (ICT). This transformation process not only introduced innovative products but also changed the way of service delivery. Mobile banking is the most popular and powerful mode of service delivery, which ensures the delivery of banking services anywhere and anytime. This article attempts to analyse the current status of research on mobile banking in order to identify the themes to be explored by future researchers. With the deft use of different inclusion and exclusion criteria and relevant and appropriate keywords, 79 journal articles published in renowned databases were selected for an in-depth review and thorough analysis. The place of study, target group focus, the theoretical models adopted and the themes considered were the basis for analysis. Most of the studies were found to have been undertaken in developing countries, and the initial adoption is the most explored area of research on mobile banking. Technology acceptance model (TAM) is the most widely used theoretical model for predicting mobile banking adoption. As the continuance intention to use mobile banking is the less explored one, there is a need to shift the research focus from initial adoption to the continuance intention to use mobile banking. Research studies on mobile banking need to be conducted among distinct groups such as the otherwise-abled, migrant workers and marginalized sections of society as they have the potential to make great contributions towards the digital economy and nation building